Hemodynamic Effects of Left Atrial or Left Ventricular Cannulation for Acute Circulatory Support in a Bovine Model of Left Heart Injury. Issue 3 (May 2015) - Kapur, Navin K.; Paruchuri, Vikram; Pham, Duc Thinh; Reyelt, Lara; Murphy, Barbara; Beale, Corinna; Bogins, Courtney; Wiener, Daniel; Nilson, James; Esposito, Michele; Perkins, Scott; Perides, George; et al.
Abstract : Our objective was to examine the hemodynamic effects of a trans-aortic axial flow catheter (Impella CP) in the left ventricle (LV) versus left atrial (LA) to femoral artery bypass using a centrifugal pump (TandemHeart: TH) in a bovine model of acute LV injury. In three male calves, we performed sequential activation of a CP then TH device in each animal. After 60 minutes of left anterior descending artery ligation, a CP was activated at maximal power. The CP was then removed and the TH activated at 5, 500 then a maximum of 7, 500 rotations per minute (RPM). The CP generated a maximum 3.1 ± 0.2 L/minute (LPM) of flow, whereas the TH at 5, 500 and 7, 500 RPM generated 3.1 ± 0.4 and 4.4 ± 0.3 LPM. At 3.1 LPM, the CP and TH reduced LV stroke work (LVSW) similarly. The TH reduced stroke volume, whereas the CP did not. The CP reduced end-systolic pressure, whereas the TH did not. At a maximum flow of 4.4 LPM, the TH provided a greater reduction in LVSW than maximal CP activation. This is the first report to compare the hemodynamic effects of trans-aortic LV unloading versus LA-to-femoral artery (FA) bypass.